2003
DOI: 10.1007/bf02703324
|View full text |Cite
|
Sign up to set email alerts
|

Micro-machining of optical glasses — A review of diamond-cutting glasses

Abstract: In order to diamond-turn optical glasses to a nanometric surface finish, it is critical to determine the transition point from brittle mode to ductile mode. This paper presents various experimental techniques to study this transition and discusses the mechanism of the surface generation. It has been recognized that tool wear is a serious issue in diamond turning of glasses. Thus, research in future should be concentrated on this field to enable the technology to be applied in commercial production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…It has been shown that if the depth of cut is lower than a certain critical depth, calculated with the undeformed chip thickness theory, ductile streaks could be obtained [5,[9][10][11][12]. For higher depth of cut, different damages can be generated.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that if the depth of cut is lower than a certain critical depth, calculated with the undeformed chip thickness theory, ductile streaks could be obtained [5,[9][10][11][12]. For higher depth of cut, different damages can be generated.…”
Section: Introductionmentioning
confidence: 98%
“…A wide range of applications have shown that UVA machining is more effective compared with its conventional process, reflected by, e.g., lower machining forces, higher machining stability, less tool wear and better surface finish. UVA machining is particularly advantageous in the surfacing of difficult-to-cut materials [1][2][3][4][5][6][7][8][9][10][11][12][13]. As the mechanisms of the UVA processes (e.g., cutting, drilling and milling) can be better elucidated by the UVA cutting, our discussion in this paper will focus on the UVA cutting unless otherwise required.…”
Section: Introductionmentioning
confidence: 99%
“…SPDT was a chosen as the material removal method in this study as it offers better accuracy, quicker fabrication time and lower cost when compared to grinding and polishing (Fang et al, 2003). The high demand in optical and electronic industry has been consistently pushing=breaking the barriers in various nanotechnology areas such as SPDT.…”
Section: Resultsmentioning
confidence: 99%